Lógos e Eä: a individuação junguiana na obra de J.R.R. Tolkien - Perassoli Junior, Sérgio Ricardo (2022)
This research aims to analyze and investigate the individuation process in the fictional universe composed by John Ronald Reuel Tolkien. Our objects of study are the novel The Lord of The Rings (1954-1955) and some narratives present in The Silmarillion (1977). The individuation process, a concept developed by Swiss psychiatrist Carl G. Jung, is characterized as the psyche's tendency to find balance and completeness. This tendency manifests itself in the journey of the characters Beren, Lúthien, Eärendil, Elwing, Galadriel, Aragorn, and Frodo, to point out a few examples. Tolkien's narratives also suggest that the individuation takes place not only in characters or through characters but constitutes an element that shapes the universe created by the author. To enrich the analysis, literary theorists such as Northrop Frye and Gaston Bachelard, who were influenced by Carl Jung's archetypal psychology, will be presented. If necessary, we will also examine Freudian psychoanalysis to understand the rich and complex narrative of the author. This research also intends to illustrate the importance of Jung's ideas and concepts for literature studies and criticism itself.